Transformasi manajemen pendidikan sebagai kunci peningkatan mutu sekolah - Sari, Devi Indah (Jurnal Madako Education, 2024)
One of the keys to the sustainable development of society and the nation is quality education. Educational management plays a crucial role in improving the quality of education in schools. Educational management encompasses planning, organising, directing, and controlling various aspects of education. Planning involves setting academic goals, developing curricula, and planning learning activities. Organising includes allocating resources, assigning tasks, and forming effective work teams. Directing involves coaching and developing students, and controlling learning activities. Educational management improves the quality of education through strong and visionary leadership, effective resource management, relevant curriculum development, ongoing evaluation, and strong collaboration between schools, teachers, parents, and the community. In the digital age, the appropriate use of information and communication technology is also crucial to improving the quality of education. To enhance the quality of education in schools, educational management must adopt an inclusive, responsive to change, and student-centred approach. This means prioritising teacher professional development, closely monitoring the learning process, and increasing parental participation and involvement in their children's education.